Managing and resolving workplace conflict - Lipsky, David B., 1939-; Avgar, Ariel C.; Lamare, J. Ryan; Gollan, Paul; Lewin, David, 1943- (Advances in industrial and labor relations ;, 2016)
In recent years many employers in the U.S., Great Britain, Ireland, and elsewhere, often in partnership with their unions, have turned to new approaches to managing and resolving workplace disputes. In the U.S. this movement is often called "alternative dispute resolution" (ADR), an approach that involves the use of mediation, arbitration, and other third-party dispute resolution techniques, rather than litigation, to resolve workplace disputes. Some employers have established so-called "conflict management systems," a pro-active, strategic approach to handling workplace conflict. This volume contains chapters by some of the worlds leading scholars of workplace dispute resolution and conflict management as well as chapters by emerging younger scholars in these fields. The chapters present original research that combines cutting-edge thinking about the theoretical dimensions of ADR and conflict management along with rigorous empirical analyses of real-life data.